Identifying Targeted Strategies to Improve Smoking Cessation Support for Cancer Patients. Issue 11 (November 2015) - Warren, Graham W.; Dibaj, Shiva; Hutson, Alan; Cummings, K. Michael; Dresler, Carolyn; Marshall, James R.
Abstract : Introduction: Although smoking causes adverse outcomes in cancer patients, most oncology providers do not regularly provide smoking cessation support. The purpose of this study was to identify key areas that can be targeted to improve delivery of evidence-based cessation support for cancer patients. Methods: In 2012, the International Association for the Study of Lung Cancer surveyed members asking about tobacco assessment and cessation practices for cancer patients. Responses from 1153 physician level oncology providers were analyzed to evaluate the effects of respondent demographics, tobacco use perceptions, and perceived barriers to providing cessation support on practice patterns. Results: Respondents from the United States generally reported higher rates of asking about tobacco use, advising patients to quit, and assisting patients in quitting smoking. Work setting, time since completing a terminal degree, percent of time devoted to clinical care, and history of tobacco use were generally associated with asking about tobacco use and advising patients to quit, but not associated with discussing medications or actively treating patients. The dominant multivariate barriers to providing cessation support were a lack of clinician education or experience and lack of available resources to refer patients for smoking cessation support. Patient resistance to treatment, inability for patients to quit smoking, or feeling that smoking was not an important part of cancer outcome or cancer care had less meaningful associations with providing support. Conclusions: Improving clinician education and developing dedicated resources to provide cessation support were identified as ideal targets to address for improving cessation support for cancer patients.